Analisis Penempatan Node Sensor Terhadap Jarak Pengambilan Data Pada Media Tanah - Rahman Faisal; Roghib Muhammad Hujja (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2019)
Badan Nasional Penanggulangan Bencana (BNPB) describes the number of casualties, property and environment resulting from landslides. Wireless sensor network technology can minimize the loss of life, property and environment [1, 2]. Wireless sensor networks are prone to interference, especially in data transmission. Transmission of wireless sensor data can be disrupted if material is blocked. Slides that are easily landslide in Indonesia consist mainly of soil material [3]. Soil is one material that can interfere with wireless sensor data transmission and is influenced by aspects such as temperature, weather, soil composition, soil moisture, and soil homogeneity [4, 5]. This study focuses on analyzing the effect of sensor node placement on data transmission distance on WiFi-based soil material. The results of the analysis of the placement of sensor nodes planted in the ground resulted in an average percentage attenuation of signal strength every 5 cm depth increase in soil material was 4.90%.